(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In the primary processing of cotton, efficient cleaning of the fiber from mechanical impurities is a crucial stage that determines the quality of the final textile product. In modern textile manufacturing, improving the cleaning process, implementing energy-saving technologies, and minimizing the human factor are important scientific and practical objectives. The aeromechanical method of cleaning cotton fibers is based on separating impurities through the action of an air stream. This method ensures high cleaning efficiency with minimal mechanical damage to the fiber. This thesis presents the development of a mathematical model of the aeromechanical cleaning process, focusing on the optimization of airflow parameters, drum speed, and their influence on cleaning efficiency.